(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This scientific article provides a comprehensive analysis of the development trends of the restaurant industry in Uzbekistan and its impact on the tourism sector. Particular attention is paid to the role of restaurants in the formation of gastronomic tourism, improvement of service quality, implementation of innovative technologies, and promotion of the national culinary brand. The article also identifies existing challenges and proposes effective solutions.